LTE-A Cellular Networks Multi-hop Relay for Coverage, Capacity and Performance Enhancement - Yahya, Abid (Springer International Publishing : Imprint: Springer, 2017)
In this book, three different methods are presented to enhance the capacity and coverage area in LTE-A cellular networks. The scope involves the evaluation of the effect of the RN location in terms of capacity and the determination of the optimum location of the relay that provides maximum achievable data rate for users with limited interference at the cell boundaries. This book presents a new model to enhance both capacity and coverage area in LTE-A cellular network by determining the optimum location for the RN with limited interference. The new model is designed to enhance the capacity of the relay link by employing two antennas in RN. This design enables the relay link to absorb more users at cell edge regions. An algorithm called the Balance Power Algorithm (BPA) is developed to reduce MR power consumption. The book pertains to postgraduate students and researchers in wireless & mobile communications. Provides a variety of methods for enhancing capacity and coverage in LTE-A cellular networks Develops an algorithm to reduce power consumption Presents approaches for applications such as gaming, playing and watching TV on a smart phone, and conducting low cost calls.